ANALISIS KOMPETENSI PEDAGOGIK DAN KESIAPAN GURU SEKOLAH DASAR DALAM IMPLEMENTASI KURIKULUM 2013 DI KABUPATEN MUNA BARAT - Sarimu, La; Harimu, La; Ruslin, Ruslin (Halu Oleo University)
This study aims to analyze (1) pedagogic competence of elementary school teachers in the implementation of Curriculum 2013; (2) the readiness of elementary school teachers in the implementation of Curriculum 2013; (3) the readiness of learning supporting facilities and infrastructures; (4) learning plan 2013 curriculum developed by elementary school teachers; (5) implementation of the 2013 curriculum learning by elementary school teachers; and (6) assessment of curriculum 2013 by elementary school teachers. This type of research is descriptive research. The type of data used in this study is descriptive quantitative and qualitative.The sample of this research is teacher of class I and IV which amounts to 40 teachers. Sampling technique in this research use purposive sampling. The instruments used are written test, questionnaire, observation sheet and documentation.The results showed that (1) pedagogic competence based on test results with an average value of 56.25 is in the category enough; (2) teacher pedagogic competence based on teacher questionnaire with average score 73,48 are in good category; (3) teacher preparedness based on questionnaire with average value 62,85 are in enough category; (4) readiness of facilities and infrastructure of learning support based on observation guidance with average value 79,3 is in good category; (5) learning planning based on the result ofÂ study with the average score of 73.42 is in good category; and(6) implementation of learning based on observation guidance with average value 69,57 are in enough category; 7) the assessment of teacher based questionnaires with an average score of 63.75 are in enough categories.Â Keywords: Pedagogic Competency, Teacher Readiness, Readiness of Facilities and Infrastructure, Learning Planning, Learning Implementation, Learning Assesment.